PERSILANGAN INTERSPESIFIK ANGGREK HITAM (Coelogyne pandurata) DENGAN ANGGREK MUTIARA (Coelogyne asperata) - Deswiniyanti, Ni Wayan; Lestari, Ni Kadek Dwipayani (Metamorfosa: Journal of Biological Sciences, 2017)
Black orchid ( Coelogyne pandurata ) and Pearl orchid ( Coelogyne asperata ) are endemic orchid from Kalimantan forest, shape and color suitable as ornamental flower. Many people collected the orchids from the wild for commercial purpose but not much effort on their propagation. To prevent population decreased, propagation and production of new varities via interspesific hybridisation need to be done. An important step required in plant breeding is to obtain cross compatiblity. Cross compatibility of some orchids from Indonesia are not known, including compatibility of Coelogyne pandurata x Coelogyne asperata . Information on compatibility and fertility is very important to produce good quality seed as propagation material. In this research pollination was performed on orchid plants at 2 until 5 day after flowering and pollination was done in the morning. There are three replicates for each pollination.  Pollination was done with C. pandurata (black orchid) as male parent and C. asperata (pearl orchid) as female parent. The results showed that successful pollination was obtained from pollination at 2 days after flowering. Seed capsule was harvested at 3 months after pollination but not yet perfectly ripe. Seed germination employed in vitro method on Vacin & Went (VW) and VW with modification media. Seed from C. pandurata x C. asperata abled to germinate on VW media with addition of 0,1 mg/l auxin and 0.1 mg/l cytokinin and germinated 9 weeks after planting.
Keywords: Plant Tissue Culture, Hybridization, Media VW, fertility